Comparison of artificial neural network and multiple regression for partial discharge sources recognition - Abubakar Masud A.; Muhammad-Sukki F.; Albarracin R.; Alfredo Ardila-Rev J.; Hawa Abu-Bakar S.; Fadilah Ab Aziz N.; Bani N.A.; Nabil Muhtazaruddin M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Defects; Linear regression; Neural networks; Regression analysis; Insulation defects; Multiple linear regressions; Multiple regressions; Offline; Partial discharge sources; Pd detections; PD measurements; Training and testing; Partial discharges